Heterotic patterns of early maturing maize inbred lines in Strigafree and Strigainfested environments - Agbaje, S.; Badu-Apraku, Baffour; Fakorede, M.A.B. (2008)
Separation of inbred lines of maize (Zea mays L.) into contrasting heterotic groups is of critical importance in determining the potential of lines for the development of high-yielding hybrids. Forty-two Striga resistant, early maturing white endosperm inbred lines were crossed to two intermediate maturing, white endosperm tester lines (1368 and 9071) to generate 84 testcrosses.The 84 testcrosses plus 4 checks were evaluated in Striga-infested environments at Mokwa and Abuja, and in Striga-free environments at Mokwa and Ile-Ife in Nigeria in 2005. Significant general combining ability (GCA) andspecific combining ability (SCA) effects for grain yield were observed. Thirteen of the 42 lines could be classified into heterotic groups based on the SCA effects and testcross mean grain yield in Striga-free environments. Under Striga-infested conditions, 12 lines were classified into heterotic groups. Four of the lines (TZE-W Pop C0S6inb50-2-4, TZE-W Pop × LD S6Inb6 from the 1368 group and TZE-W Pop C0S6Inb12-2-2, and TZE-W Pop C0S6Inb50-3-4 from the 9071 group) maintained their heterotic groups in both Striga-free and Striga-infested environments. Three testcross hybrids (TZE-W Pop C0S6Inb50-2-4 x 1368; TZE-W Pop C0S6Inb50-3-4 x 9071 and TZE-WPop C0S6Inb151-1-2 x 9071) had consistently positiveSCA effects in the two environments and are, thereforepotentially good hybrids for both the savanna and forest ecologies.